2014
DOI: 10.1371/journal.pone.0089213
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Long-Term Care Services among the Elderly: A Population-Based Study in Taiwan

Abstract: ObjectivesThe aim of the study was to investigate determinants of long-term care use and to clarify the differing characteristics of home/community-based and institution-based services users.DesignCross-sectional, population-based study.SettingUtilizing data from the 2005 National Health Interview Survey conducted in Taiwan.ParticipantsA national sample of 2,608 people (1,312 men, 1,296 women) aged 65 and older.MeasurementsThe utilization of long-term care services (both home/community- and institution-based s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
76
4
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(106 citation statements)
references
References 30 publications
17
76
4
9
Order By: Relevance
“…The research by Wu et al conducted in Taiwan among people at the age of 65 years and older showed, like the presented research, that the essential determinants of long-term care were: age, living alone, stroke, and cognitive impairment [15].…”
Section: Discussionsupporting
confidence: 72%
“…The research by Wu et al conducted in Taiwan among people at the age of 65 years and older showed, like the presented research, that the essential determinants of long-term care were: age, living alone, stroke, and cognitive impairment [15].…”
Section: Discussionsupporting
confidence: 72%
“…When applying Andersen's model to home care use, the preeminence of need factors was obvious. The association with limitations in ADL/IADL has already been extensively established and, in our case, was further strengthened by taking into account their evolution over the study period [7,8,[17][18][19][20][21][22][23]. In a logistic regression model including this variable, the number of other need factors remaining significantly associated with home care utilization was actually limited.…”
Section: Discussionmentioning
confidence: 69%
“…First, the finding of the increased intention to use LTC facilities compared to prior research demonstrates the growing need for LTC facilities. This growing preference for LTC facilities has been taking place in other Asian countries as well, such as China (Zhan et al 2011), Taiwan (Lee et al 2010; Wu et al 2014), and Japan (McCormick et al 2002; Tsutsui and Muramatsu 2005). Despite the pressing need for LTC facilities, the current number of LTC facilities in Korea is not sufficient to respond to such growing LTC needs (Kim and Kim 2004; Kim et al 2012).…”
Section: Discussionmentioning
confidence: 99%